Testing the Influence of Logistics Service Quality on Customer Intentions to Reuse the Logistics Industry for Shipping Services Through the Mediation of Customer Satisfaction - Fikra Terisha Azzikra; Immanuel Zai (Universitas KH. Abdul Chalim Mojokerto, 2025)
Logistics services play a crucial role in enhancing competitiveness, particularly in the e-commerce sector. This study aims to assess the impact of operational quality, resource quality, information quality, personal contact quality, and customization quality on customer satisfaction and reuse intention in utilizing logistics services. The research employed a quantitative method, gathering data from 392 respondents who are e-commerce users utilizing logistics services. The findings indicate that customization quality and information quality do not significantly influence customer satisfaction. However, the three main aspects of logistics service quality—operational quality, personal contact quality, and resource quality—positively and significantly affect customer satisfaction. Furthermore, customer satisfaction is proven to be the primary factor influencing reuse intention in logistics services. These findings highlight the importance of comprehensive service quality management, particularly in enhancing direct interactions with customers.